2009
DOI: 10.1177/0734282909341019
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Diagnosis of “Gifted/LD”: Characterizing Postsecondary Students With Learning Disability Diagnoses at Different IQ Levels

Abstract: Increasing numbers of students are being diagnosed as simultaneously gifted and having a learning disability, although the identification procedures and characteristics of these students are matters of continuing debate. In the present study, postsecondary students with learning disability diagnoses ( N = 357) were grouped according to their IQ scores, and the groups’ cognitive and achievement characteristics were explored, with special attention to the proportions of each group that would meet various objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
1
16
1
Order By: Relevance
“…Altogether, these findings provide very little objective support for either students’ accommodations or the disability diagnoses upon which they are based. Our findings are consistent with previous research involving students with learning disabilities at public, 4-year colleges who show above-average intellectual abilities and relative, but not normative, deficits in academic skills (Lovett & Sparks, 2010). However, our findings contrast with previous research involving community college students with disabilities, who tend to have current diagnoses, long-standing histories of academic problems, and normative deficits in broad academic skills that interfere with their educational and occupational functioning (Weis et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Altogether, these findings provide very little objective support for either students’ accommodations or the disability diagnoses upon which they are based. Our findings are consistent with previous research involving students with learning disabilities at public, 4-year colleges who show above-average intellectual abilities and relative, but not normative, deficits in academic skills (Lovett & Sparks, 2010). However, our findings contrast with previous research involving community college students with disabilities, who tend to have current diagnoses, long-standing histories of academic problems, and normative deficits in broad academic skills that interfere with their educational and occupational functioning (Weis et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…L. Sparks & Lovett, 2013). Moreover, students with the highest cognitive abilities were least likely to show normative deficits in academic achievement, difficulties with academic performance, or other limitations in academic functioning (Lovett & Sparks, 2010).…”
Section: Students With Disabilities At Selective Private Collegesmentioning
confidence: 99%
“…For instance, the observation that Swanson and Hsieh [17] and Hatcher et al [14] found no differences in general intelligence or problem solving between students with and without reading problems may be a consequence of the fact that British and American universities select their students on the basis of SAT-scores (US) and A-levels (UK). Indeed, Lovett and Sparks [32] noticed that a discrepancy between general intelligence and reading skills in American university students with reading disabilities is often due to average text reading skills combined with above-average IQ. Such a pattern might be a direct consequence of the admission criteria.…”
Section: Introductionmentioning
confidence: 99%
“…However, as we pointed out, there might be some students who may not receive the appropriate assistance because of its inappropriate approaches. Recent study proposes that making a precise diagnosis is essential to helping students with LD [16]. In addition, we may include some students who do not actually have LD, or students who were determined to have LD because of improper measurement methods.…”
Section: Resultsmentioning
confidence: 99%